Behavior and Performance of GFRP Reinforced Concrete Columns with Various Types of Stirrups. (1st October 2015) - Prachasaree, Woraphot; Piriyakootorn, Sitthichai; Sangsrijun, Athawit; Limkatanyu, Suchart
Abstract : Fiber reinforced polymer (FRP) composites are gaining acceptance in concrete structural applications due to their high ratio of strength/stiffness to self-weight and corrosion resistance. This study focused on the structural behavior and the performance of concrete columns internally reinforced with glass fiber reinforced plastic (GFRP) rebars. Twelve series of concrete columns with varied longitudinal reinforcement, cross section, concrete cover, and type of lateral reinforcement were tested under compression loading. The results show that the amount of GFRP longitudinal and lateral reinforcement slightly affects the column strength. The lateral reinforcement affects the confining pressure and inelastic deformation, and its contribution to the confined compressive strength increases with the GFRP reinforcement ratio. In addition, the confining pressure increases both concrete strength and deformability in the inelastic range. The confinement effectiveness coefficient varied from 3.0 to 7.0 with longitudinal reinforcement. The average deformability factors were 4.2 and 2.8 with spirals and ties, respectively. Lateral reinforcement had a more pronounced effect on deformability than on column strength.